Pemaknaan Hidup Pewaris Sate In Bur Generasi Ke-4 di Kabupaten Lima Puluh Kota - Indah Rahma Wati; Yanladila Yeltas Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Family businesses are not only viewed as sources of economic profit but also as inheritances carrying historical and cultural values. This study focuses on the life meaning of the fourth-generation heir of Sate In Bur in Lima Puluh Kota Regency in continuing the family business that has existed for several decades. The purpose of this research is to explore the subjective meaning formed through the heir’s experiences in facing the challenges of maintaining a family enterprise. This study employs a qualitative method with a phenomenological approach to deeply understand the reality experienced by the subject. The research subject was selected purposively based on the criterion of being an active heir currently managing the business. Data were collected through in-depth interviews and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal five main themes: facing declining income due to market competition, expanding business reach through innovation and digital promotion, strengthening business continuity as a moral responsibility to the family, preserving culinary heritage and local culture, and improving product quality to maintain customer loyalty. These findings indicate that the heir’s life meaning is not solely oriented toward economic aspects but also encompasses family values, cultural identity, and social responsibility in sustaining the longevity of the family business.